Cumulative exergy analysis of lignocellulosic biomass to bio-jet fuel through aqueous-phase conversion with different lignin conversion pathways. (15th February 2023) - Zhang, Qiongyin; Xiao, Jun; Hao, Jingwen
Abstract: Lignocellulosic biomass conversion to bio-jet fuel is beneficial for reducing the depletion of fossil fuel. This study presented and compared the two different pathways of lignin in corn stalk to bio-jet fuel via aqueous-phase conversion based on the process simulation approach and life cycle cumulative exergy analysis. The results show that the pathway of lignin one-step conversion (LJA) can obtain a higher bio-jet fuel yield and cumulative exergy efficiency than lignin two-step conversion (LJC). Moreover, biomass conversion to bio-jet fuel with self-supplied hydrogen is beneficial to the conversion of low-quality biomass into high-quality bio-jet fuel and the decrease in fossil fuel consumption. Under the optimal parameters, corn stalk aqueous-phase conversion to bio-jet fuel with external-supplied hydrogen can achieve the largest bio-jet fuel yield (142.7 kg/t-bio) and cumulative exergy efficiency of system (29.3%). The sensitivity analyses show that the hydrolysis efficiency of lignin has the most influence on the cumulative exergy efficiency of bio-jet fuel, while the furfural yield from hemicellulose has the lowest impact. When the consumption of chemicals and steam is considered, it is significant to reduce the stripping steam to furfural ratio for the cumulative exergy efficiency and reduce the consumption of methanol and sulfuric acid for the renewability. Highlights: Two pathways of lignin aqueous-phase conversion to bio-jet fuel are compared. Life cycle cumulative exergy analysis of biomass to bio-jet fuel is conducted. Lignin one-step conversion to bio-jet fuel exhibits a better resource performance. Self-supplied hydrogen increases energy-quality improvement rate and renewability.